The Effect of Augmented Reality Learning Media on Improving Elementary School Students’ Creative Thinking Skills - Jihan Nurfadhila; Nur Asyiah; Aliet Noorhayati Sutisno (FKIP - Universitas Riau, 2026)
This research is motivated by the low level of creative thinking of students caused by the non-interactive nature of learning IPAS. The purpose of this study is to find out the extent of the influence of Augmented Reality learning media on social studies learning on students' creative thinking skills. The method used in this study is a quantitative method with a pre-experimental design. The subjects of this study were 18 elementary school students. Data analysis used descriptive statistics, N-gain, normality test, paired sample t-test. Based on the results of the study, it was found that the average pretest score obtained was 49, and the average posttest score was 77. The N-Gain test result was 0.5457 in the range of 0.3 ≤ g < 0.7 medium category. The normality test in the Shapiro-Wilk test for pretest data was 0.288 > 0.05, while for posttest data it was 0.670 > 0.05. The results of the paired test of the t-test sample obtained a value (Sig. 2-tailed) of 0.000 < 0.05, then H0 was rejected and H1 was accepted. The use of Augmented Reality learning media is effective in improving students' creative thinking skills through interactive and student-centered learning experiences.